2014
DOI: 10.1089/vbz.2013.1424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of a Rapid Enzyme-Linked Immunosorbent Assay in the Detection ofAnaplasma phagocytophilumAntibodies in Horses

Abstract: The aim of this study was to evaluate the performance of a commercially available rapid enzyme-linked immonosorbent assay, the Snap® 4Dx test, in the detection of Anaplasma phagocytophilum antibodies in horses. Two hundred apparently healthy horses (asymptomatic) and 244 animals showing clinical symptoms (symptomatic), were tested for A. phagocytophilum immunoglobulin G (IgG) antibodies using both the Snap® 4Dx kit and an indirect fluorescence antibody test (IFAT), with the latter serving as a comparative test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Numerous studies conducted outside Korea have also reported seropositivity for A. phagocytophilum in horses: 73% (67/90) of horses in the Czech Republic tested positive by IFAT (Praskova et al 2011); 13% (21/162) of horses in Portugal tested positive by IFAT (Ribeiro et al 2013); 13.7% (41/300) and 6.7% (20/300) of horses in Italy tested positive by IFAT and PCR, respectively (Laus et al 2013);16.3% (56/343) of horses in Tunisia tested positive by IFAT (Ben Said et al 2014); and 10.1% (45/444) and 9.0% (40/444) of horses in Italy tested positive by IFAT and ELISA, respectively (Veronesi et al 2014). The prevalence of seropositivity in the present study was lower than that reported in these studies; however, it is consistent with another Korean study that showed 2.2% (2/92) seropositivity for A. phagocytophilum in horses reared on Jeju Island, as determined by IFAT (Chae et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies conducted outside Korea have also reported seropositivity for A. phagocytophilum in horses: 73% (67/90) of horses in the Czech Republic tested positive by IFAT (Praskova et al 2011); 13% (21/162) of horses in Portugal tested positive by IFAT (Ribeiro et al 2013); 13.7% (41/300) and 6.7% (20/300) of horses in Italy tested positive by IFAT and PCR, respectively (Laus et al 2013);16.3% (56/343) of horses in Tunisia tested positive by IFAT (Ben Said et al 2014); and 10.1% (45/444) and 9.0% (40/444) of horses in Italy tested positive by IFAT and ELISA, respectively (Veronesi et al 2014). The prevalence of seropositivity in the present study was lower than that reported in these studies; however, it is consistent with another Korean study that showed 2.2% (2/92) seropositivity for A. phagocytophilum in horses reared on Jeju Island, as determined by IFAT (Chae et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A commercial ELISA kit (SNAP ® 4Dx test; IDEXX Laboratories, USA) was used to detect antibodies against A. phagocytophi- Although the SNAP ® 4Dx test was originally developed to detect canine antibodies against A. phagocytophilum, it can also be used to detect antibodies against A. phagocytophilum in blood samples from horses (Chan et al 2010;Vieira et al 2013;Veronesi et al 2014). The SNAP ® 4Dx test detects antibodies from both active infection and previous exposures to the pathogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-reactivity is arguably of greater concern in samples with low titers, and, interestingly, a reduced relative sensitivity of the pocELISA in samples with low IFAT titers for antibodies against A. phagocytophilum was previously demonstrated. 24 False-positive results due to nonspecific reactivity with antibodies against flagellin or heat shock proteins may also occur with the B. burgdorferi whole-cell IFAT. 16 In this context, it is interesting to note that Borrelia miyamotoi and Borrelia kurtenbachii have been previously reported to infect I. scapularis in Canada.…”
Section: Research-article2015mentioning
confidence: 99%
“…As stated earlier, our study is not suitable to draw any conclusions with regard to sensitivity and specificity of the employed tests in a clinical context. While there may be insufficient information to unequivocally support individual serologic tests as the "gold standard" in horses, previous studies reported high sensitivity and specificity of available serologic tests 7,23,24 when known positive and negative samples were tested. Previous reports in other populations of horses also stated much better agreement between diagnostic tests.…”
Section: Research-article2015mentioning
confidence: 99%